AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DI BADAN PENGELOLAHAN KEUANGAN DAN ASET DAERAH KOTA PADANGSIDIMPUAN - Lukman Alwi Lubis; Muhammad Arifin Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
The accountability of Padangsidimpuan city regional financial management in the Padangsidimpuan City Regional Financial and Asset Management Agency has several problems including weaknesses in the Internal Control System, non-compliance with statutory provisions, as well as problems, inefficiency, and ineffectiveness. 2019 is the fifth time that the City of Padangsidimpuan has received the title of Fair Opinion with Exceptions from the Supreme Audit Agency for North Sumatra Province. This study aims to analyze and describe the accountability of the city government, especially the City of Padangsidimpuan in managing regional finances. The method used in this study uses descriptive qualitative. Data collection techniques were carried out by interviewing and recording documents. The data that has been obtained is then analyzed qualitatively with the accountability theory approach proposed by Ellwood which is categorized to describe honesty and legal accountability, process accountability, program accountability, policy accountability. The results of the study show that in carrying out the duties and responsibilities of BPKAD employees guided by the duties and functions according to the Mayor's Regulation, the implementation of financial management activities is in accordance with the budget plan that has been made before, the Regional Revenue Policy and Expenditure Policy of the city of Padangsidimpuan are still unresolved, and the APBD preparation process, the time allotted in the procedure cannot be carried out according to the conditions in the field. The obstacle experienced by BPKD is the lack of Human Resources.